2016
DOI: 10.1089/chi.2016.0180
|View full text |Cite
|
Sign up to set email alerts
|

Hypertriglyceridemic Waist Phenotype Indicates Insulin Resistance in Adolescents According to the Clamp Technique in the BRAMS Study

Abstract: The findings suggest HTWP as an IR status in adolescents. Cutoff point standardization for gender and pubertal stage, combined with the ease of application of the method, may allow their use for screening adolescents who would most benefit from lifestyle changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…HOMA-IR [1] has been validated as a surrogate measure of insulin resistance in children and adolescents and is widely used in epidemiological studies in pediatric populations [3, 7, 8, 23]. However, it assumes that hepatic and peripheral insulin resistance are equal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HOMA-IR [1] has been validated as a surrogate measure of insulin resistance in children and adolescents and is widely used in epidemiological studies in pediatric populations [3, 7, 8, 23]. However, it assumes that hepatic and peripheral insulin resistance are equal.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, laboratory assays of plasma glucose and insulin are easier and cheaper to obtain than adiponectin measurement, which is not yet a routinely run test in public health service. Furthermore, previously, we have identified other more simple and practical methods, such as the waist circumference [8], sagittal abdominal diameter [8] and the hypertriglyceridemic waist phenotype (presence of a concomitant increase in plasma triglycerides and waist circumference) [7] that also can be used as surrogate measures of insulin resistance in this age group. The choice of the method will depend on the goals you are interested, research or clinical evaluation, the infrastructure available, the professional experience and the health service.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was a multicenter, cross‐sectional study comprising a subsample of adolescents who participated in the Brazilian Metabolic Syndrome Study (BRAMS) conducted in the southeastern region of Brazil and has been reported in detail previously . This study included an intentional non‐probabilistic sample of 520 adolescents (303 females) recruited from the Clinic of Obesity in Children and Adolescents at Clinical Hospital of Campinas University, and from the Health Units, public schools, and institutions offering educational programs for adolescents.…”
Section: Methodsmentioning
confidence: 99%
“…The study of the HTGW phenotype, especially in children, has shown epidemiological relevance, since the atherosclerotic process begins in childhood and negatively influences the quality of life in adulthood, due to increased morbidity and mortality. 17,18 The frequency of the phenotype in this investigation was 23.5%, showing that the population of children and adolescents with T1DM has followed the profile of non-carriers, with an increase in overweight, including in the abdominal region, which is probably a reflection of the nutritional transition process that has affected different age groups in both developed and developing countries. 19 No research has evaluated HTGW in pediatric T1DM patients, and studies are limited to samples of healthy children and adolescents.…”
Section: Discussionmentioning
confidence: 57%